2022
DOI: 10.1097/aln.0000000000004240
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Power: Correlate or Cause of Ventilator-induced Lung Injury?

Abstract: This editorial accompanies the article on p. 41. This article has an audio podcast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…It suggests that the relationship between these parameters and PRF is not simply an expression that patients with poor respiratory mechanics, and therefore high mechanical power and ΔP, are at higher risk of adverse pulmonary outcomes (36). These findings thereby support a potential causative effect in previous studies (2, 4, 6, 15, 37), which has been the subject of debate (38). Even while effect sizes, as measured by aORs, were slightly diminished after exact matching for patients’ respiratory system compliance, our findings suggest that patients’ risk for PRF when receiving mechanical power greater than or equal to 6.7 J/min, or a ΔP greater than or equal to 15.0 cm H 2 O, increases by about 30% as compared with patients with values below these cutoffs.…”
Section: Discussionsupporting
confidence: 89%
“…It suggests that the relationship between these parameters and PRF is not simply an expression that patients with poor respiratory mechanics, and therefore high mechanical power and ΔP, are at higher risk of adverse pulmonary outcomes (36). These findings thereby support a potential causative effect in previous studies (2, 4, 6, 15, 37), which has been the subject of debate (38). Even while effect sizes, as measured by aORs, were slightly diminished after exact matching for patients’ respiratory system compliance, our findings suggest that patients’ risk for PRF when receiving mechanical power greater than or equal to 6.7 J/min, or a ΔP greater than or equal to 15.0 cm H 2 O, increases by about 30% as compared with patients with values below these cutoffs.…”
Section: Discussionsupporting
confidence: 89%
“…After the univariate analysis, higher intraoperative FiO 2 , driving pressure, and average inspiratory pressure during OLV were observed in patients with PPCs. Whether more invasive ventilatory settings and higher intraoperative oxygen demand reflect the effects of preexisting structural lung disease [ 21 ], or whether it may contribute to ventilator-induced injury, remains unclear in our study and would require further investigation considering the complexity of ventilator-induced injury in thoracic surgery [ 22 , 23 ]. If invasive ventilation remains, despite trials of optimization, it could identify patients at risk and trigger necessary perioperative measures, such as admission to intensive care, or intensified chest and general physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hyperperfusion and fluid overload have been shown to be causative of PPCs in thoracic surgery and pneumonectomy patients [ 22 , 27 , 28 ]. The concept of restrictive fluid management in lung resection surgery is well established, although the thresholds are not clear, and postresection lung injury is not limited to the intraoperative fluid volume alone [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, exploratory analyses revealed that males were less likely to require PMV despite higher MP, demonstrating significantly lower power density (owing to higher dynamic compliance) than female recipients. Given that MP is thought to significantly contribute to ventilator-induced lung injury [ 6 , 43 ], the question arises whether MP is a cause or correlate of impaired respiratory mechanics associated with inferior outcomes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%